2018
DOI: 10.1007/s00712-018-0623-3
|View full text |Cite
|
Sign up to set email alerts
|

Progressive taxation as an automatic destabilizer under endogenous growth

Abstract: It has been shown that in an otherwise standard one-sector real business cycle model with an indeterminate steady state under laissez faire, su¢ ciently progressive income taxation may stabilize the economy against aggregate ‡uctuations caused by agents'animal spirits. We show that this previous …nding can be overturned within an identical model which allows for sustained endogenous growth. Speci…cally, progressive taxation may operate like an automatic destabilizer that leads to equilibrium indeterminacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, within the globalized economic system, members of the "Club of Rome" recommended [7]: d) to increase taxes on large corporations, for this purpose some international cooperation is possible to limit or expand tax horizons, including the financial and banking sectors of economies; deprivation or introduction of certain privileges regarding the taxation of financial transactions, value added, commercial real estate, dividend tax, environmental pollution, negative externalities that affect the activities of such companies, such as the use of fossil fuels, fuels, raw materials that add greenhouse gas emissions ; e) a gradual increase in inheritance taxes (even up to 100%) through the SHS Web of Conferences 92, 0 (2021) Globalization and its Socio-Economic Consequences 2020 9002 https://doi.org/10.1051/shsconf/20219209002 revision by governments of property laws, based on the beliefs of Theodore Roosevelt, Adam Smith, Thomas Payne and Locke [7], that each generation cannot bind itself and have no right to property of its descendants, because the expansion of property rights is quite unnatural. Therefore, such taxes should eliminate such social anomalies; Another mechanism for reforming the tax system, which is currently being discussed in recognized international economic and financial sources [8,9,10,11] is e) the introduction of progressive taxation [9,10], which concerns not only the introduction of a progressive scale of tax revenues [8], but also the progress of views on taxes on the regulation of interest rates at the societal level [9]; g) focus on a differential approach to taxation [10], using well-known empirical trends, that only low taxation stimulates economic development and vice versa -high taxation leads to forced loss of welfare; h) taking into account the need for optimal tax policy [11], which provides for optimal access to reproductive resources, use of working time and produce socially necessary products.…”
Section: Resultsmentioning
confidence: 99%
“…However, within the globalized economic system, members of the "Club of Rome" recommended [7]: d) to increase taxes on large corporations, for this purpose some international cooperation is possible to limit or expand tax horizons, including the financial and banking sectors of economies; deprivation or introduction of certain privileges regarding the taxation of financial transactions, value added, commercial real estate, dividend tax, environmental pollution, negative externalities that affect the activities of such companies, such as the use of fossil fuels, fuels, raw materials that add greenhouse gas emissions ; e) a gradual increase in inheritance taxes (even up to 100%) through the SHS Web of Conferences 92, 0 (2021) Globalization and its Socio-Economic Consequences 2020 9002 https://doi.org/10.1051/shsconf/20219209002 revision by governments of property laws, based on the beliefs of Theodore Roosevelt, Adam Smith, Thomas Payne and Locke [7], that each generation cannot bind itself and have no right to property of its descendants, because the expansion of property rights is quite unnatural. Therefore, such taxes should eliminate such social anomalies; Another mechanism for reforming the tax system, which is currently being discussed in recognized international economic and financial sources [8,9,10,11] is e) the introduction of progressive taxation [9,10], which concerns not only the introduction of a progressive scale of tax revenues [8], but also the progress of views on taxes on the regulation of interest rates at the societal level [9]; g) focus on a differential approach to taxation [10], using well-known empirical trends, that only low taxation stimulates economic development and vice versa -high taxation leads to forced loss of welfare; h) taking into account the need for optimal tax policy [11], which provides for optimal access to reproductive resources, use of working time and produce socially necessary products.…”
Section: Resultsmentioning
confidence: 99%
“…(), Nourry et al . (), Chen and Guo (, , , , , ), Anagnostopoulos and Giannitsarou (), Gokan (), Xue and Yip (), and Abad et al . (), among many others.…”
mentioning
confidence: 99%
“…Artificial intelligence (AI) could promote the technological progress of society through "machine learning" and could inspire support for innovative technologies despite the fact that AI itself is considered to be the result of continuous technological advancements (Brynjolfsson et al, 2017). Chen et al (2019) confirmed through a dynamic general equilibrium model that artificial intelligence could help improve the speed of technological progress.…”
Section: Theory and Hypothesismentioning
confidence: 99%